Relevansi Dinding Baca dalam Menumbuhkan Literasi Sosial Siswa di Saengprathip Wittaya Mulniti School Thailand - Rodliyah, Siti; Shobirin, Ma'as; Martanti, Fitria (IJTIMAIYA: Journal of Social Science and Teaching, 2021)
The focus in this research is related to the implementation of the reading wall as an effort to foster the literacy tradition of grade I students at MI Saengprathip Wittaya Mulniti School Thailand. This research uses qualitative research methods. The results showed that the implementation of the reading wall at MI Saengprathip Wittaya Mulniti School Thailand has 5 stages. The first stage, gives 60 minutes to read. The second stage, summarizes what has been read from the reading wall, the third stage is working on the problem. The fourth stage recounts what has been read in front of the class. The fifth stage provides appreciation for students who tell stories in front of the class, and appreciation for those who have worked on questions with the best scores. The role of grade I teachers in implementing the reading wall is as a companion and facilitator. In addition to assisting students in reading wall activities as a literacy process, the teacher also acts as a facilitator. The obstacle that occurs in implementing the reading wall as an effort to foster the literacy tradition of grade I students at MI Saengprathip Wittaya Mulniti School is that classroom teachers cannot focus on making reading walls because the teacher's working hours are the same as school hours. The lack of cohesiveness of all grade I teachers makes the making of reading walls difficult if it is done without the cohesiveness of teachers between class I.